Analysis of alanine aminotransferase screening results in blood donors and quality management measures - ZANG Liang; ZHOU Lei; CHANG Le; WANG Lunan (Zhongguo shuxue zazhi)
[Objective] To explore quality issues and quality management measures in alanine aminotransferase (ALT) testing, aiming to improve consistency and accuracy of ALT test results by analyzing the outcomes from different pre-donation screening methods and different sample sources. [Methods] Data were collected from 58 blood collection and supply institutions across China. ALT test results from donor samples analyzed by dry chemistry analyzers, semi-automatic biochemical analyzers, and automatic biochemical analyzers were compared, focusing on the influence of venous versus capillary blood samples on testing accuracy. By comparing results from pre-donation screening with laboratory testing, the current state of quality management for different methods and sample types was assessed. Differences in ALT unqualified rates between laboratories were analyzed, and quality improvement strategies were proposed accordingly. [Results] No significant differences were found in laboratory ALT unqualified rates between venous and capillary blood samples during pre-donation screening across different analytical methods (P>0.05). However, laboratory ALT unqualified rates were consistently lower for venous blood compared to capillary blood, regardless of the testing method used (P<0.05). Notable differences in quality control were observed among various blood collection and supply institutions (P<0.05). [Conclusion] Minimal differences were observed between pre-donation ALT screening results obtained by the three analytical methods and laboratory test outcomes; thus, blood stations can select an appropriate testing method according to their specific conditions. Pre-donation screening using venous blood samples demonstrated superior reliability in quality control compared to capillary blood samples. Significant variations in ALT unqualified rates among blood stations suggest that blood collection and supply institutions should emphasize quality management at both the pre-donation screening and laboratory testing stages. Measures such as optimized standardized operating procedures, regular equipment calibration and maintenance, proficiency testing, internal quality control, inter-system comparisons, and enhanced personnel training and evaluation should be implemented to ensure consistent and stable screening results, thereby reducing ALT unqualified rates.